2017
DOI: 10.1002/1873-3468.12634
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose sensing through nascent peptide‐meditated ribosome stalling at the stop codon of Arabidopsis bZIP11 uORF2

Abstract: Arabidopsis bZIP11 is a transcription factor that modulates amino acid metabolism under high-sucrose conditions. Expression of bZIP11 is downregulated in a sucrose-dependent manner during translation. Previous in vivo studies have identified the second upstream open reading frame (uORF2) as an essential regulatory element for the sucrose-dependent translational repression of bZIP11. However, it remains unclear how uORF2 represses bZIP11 expression under high-sucrose conditions. Through biochemical experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(93 citation statements)
references
References 49 publications
4
56
0
Order By: Relevance
“…With regard to the control of UBC34, it was found that its promoter contains four predicted binding sites for the GBF6 transcription factor (40), which is light-regulated (41) and can act as a sucrose sensor (42). This provides an exciting hypothesis for the long-proposed link between sucrose levels and SUC2 activity (8,43).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the control of UBC34, it was found that its promoter contains four predicted binding sites for the GBF6 transcription factor (40), which is light-regulated (41) and can act as a sucrose sensor (42). This provides an exciting hypothesis for the long-proposed link between sucrose levels and SUC2 activity (8,43).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing Suc levels promote ribosome stalling on the CPuORF and, consequently, due to steric hindrance on the 59 leader, ribosomes translating or scanning the uORF are unable to reach and translate the mORF ( Fig. 1; Juntawong et al, 2014;Hou et al, 2016;Yamashita et al, 2017). Single amino acid mutations in the CPuORF abolish Suc-dependent ribosome stalling (Rahmani et al, 2009;Yamashita et al, 2017).…”
Section: Sucmentioning
confidence: 99%
“…1; Juntawong et al, 2014;Hou et al, 2016;Yamashita et al, 2017). Single amino acid mutations in the CPuORF abolish Suc-dependent ribosome stalling (Rahmani et al, 2009;Yamashita et al, 2017). Thus, the CPuORF peptide and not the nucleotide sequence plays a role in ribosome stalling.…”
Section: Sucmentioning
confidence: 99%
“…Suc, polyamines, thermospermine, phosphocholine, ascorbate, galactinol, and boron). The stalling of ribosomes along these CPuORFs or at their stop codons is confirmed in ribosome-footprinting studies and is dependent upon the encoded peptide and metabolic status (Yamashita et al, 2017;van der Horst et al, 2019). Ribosome stalling also can occur in a metabolite-specific manner during mORF translation, as S-adenosyl-L-Met promotes ribosome stalling on CYSTATHIONINE GAMMA SYNTHASE1 (CGS1) mRNA, triggering its degradation.…”
Section: Upstream Open Reading Frame Control Of Translationmentioning
confidence: 89%